1983
DOI: 10.1097/00132586-198304000-00059
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia. A New Concept of Postoperative Pain Relief

Abstract: This report concerns evaluation of patient-controlled analgesia (PCA) in the form of two preliminary investigations. In the first study, the patient-controlled analgesia device, which consists of a pump linked to a timer so that patients can activate intravenous administration of morphine sulfate to themselves during the postoperative period, was used in seven morbidly obese patients. The amount of morphine used during the first 36 hours was found to vary between 32 and 185 mg, with a significant difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
2

Year Published

1984
1984
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
16
2
Order By: Relevance
“…A timer within the pump controls the frequency of self-adminis tration, preventing additional delivery of drug for a predetermined period after a dose (referred to as the 'lockout' interval). Adult patients in several studies [4][5][6] have shown a marked preference for this method of pain control over conventional regimens. Adults report longer-lasting relief with less sedation when they are in control of their own narcotic dosing; they also tend to use less total drug with PCA than with intermittent nurse-ad ministered analgesia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A timer within the pump controls the frequency of self-adminis tration, preventing additional delivery of drug for a predetermined period after a dose (referred to as the 'lockout' interval). Adult patients in several studies [4][5][6] have shown a marked preference for this method of pain control over conventional regimens. Adults report longer-lasting relief with less sedation when they are in control of their own narcotic dosing; they also tend to use less total drug with PCA than with intermittent nurse-ad ministered analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…More drug (morphine vs. morphine equiv alent) was used by study participants while on PCA, in contrast to other studies in adults which have shown that patients on PCA have lower medication requirements [9], Bennett et al [4] and Bollish et al [6] have noted, how ever, that patients on PCA self-administered more analgesic in the first 24 after surgery than was received by patients requesting in tramuscular injections, but that by 72 h after surgery PCA patients had given themselves less total analgesic than intramuscular pa…”
mentioning
confidence: 95%
“…The advantages of PCA opioids compared with im narcotics for abdominal surgery are subjectively better analgesia ~3-~s with equal 13 or less sedation. 16 Compared with epidural morphine, however, PCA morphine may provide inferior analgesia after cholecystectomy. 17 As in the case of the present study, side effects such as sedation may limit the maximum dose of /v opioids that are selftitrated.…”
Section: Discussionmentioning
confidence: 99%
“…It can be, therefore, said that the PCA system provided improved pain relief on smaller total drug dosages in a majority of the patients. Bennett et al (1982a) described that eleven of 12 (92%) patients in the PCA group characterized their postoperative state as comfortable" or "mildly uncomfortable", while seven of the 12 (58%) patients in the i.m. group characterized their net analgesic state favorably.…”
Section: Discussionmentioning
confidence: 99%